Bacterial contamination of frequently touched surfaces in computers in health care settings: a comparative study - Ali, Kawther (International Journal of Infection Control, 2017)
This study was conducted to detect and compare the presence of bacteria, specifically the pathogens Escherichia coli and Staphylococcus aureus (methicillin resistant and sensitive), on computer high-touch surfaces (keyboards and mouse) used at a university dental clinic, teaching hospital outpatient clinics, and a university health science centre students’ computer laboratories.Moistened sterile swab samples were obtained from 178 computers and cultured on MacConkey and mannitol salt agars, and then incubated for 48 hours at 37˚C. Representative colonies on the media were chosen, sub-cultured for purity and the species were identified using VITEK-2 and confirmed with VITEK MS when necessary. Of a total of 178 computer surfaces screened in the three locations, 97 (54.5%) were contaminated with bacteria. The differences in the total bacterial contaminations were statistically significant (P=0.001) between students’ computer laboratories (72.9%), hospital outpatient clinics (61.5%), and university dental clinics (32.8%). Staphylococcus aureus was detected on two computer keyboards and mice at two locations, the university dental clinics and the teaching hospital outpatient clinics. In addition, a sample from the teaching hospital’s outpatient clinic contained E. coli. No methicillin resistant Staphylococcus aureus (MRSA) was detected in all locations. In conclusion, computer keyboards and mice in various settings were contaminated with bacteria. Dental, medical, and university students’ laboratories settings had different overall bacterial contamination on computer keyboards and mice, but no detectable differences in S. aureus and E. coli was evident.